2017
DOI: 10.1183/13993003.02524-2016
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pulmonary vascular volume on mortality in IPF: is it time to reconsider the role of vasculature in disease pathogenesis and progression?

Abstract: Dear Sir,We were pleased to read the letter from Dr Puxeddu and co-workers, written in response to our observation that an increase pulmonary vessel volume, derived using quantitative CT analysis, strongly predicts mortality in patients with idiopathic pulmonary fibrosis (IPF). 1 Dr Puxeddu and his team highlight a selection of studies

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“… 7 , 8 There is a growing appreciation for the importance of the vasculature in the disease process, including possibly being important in the perpetuation of the fibrosis. 9 In support of this, two studies of PH medications have suggested amelioration of the fibrotic process as evidenced by placebo‐corrected improvements in the forced vital capacity. 10 , 11 …”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“… 7 , 8 There is a growing appreciation for the importance of the vasculature in the disease process, including possibly being important in the perpetuation of the fibrosis. 9 In support of this, two studies of PH medications have suggested amelioration of the fibrotic process as evidenced by placebo‐corrected improvements in the forced vital capacity. 10 , 11 …”
Section: Introductionmentioning
confidence: 92%
“…Pulmonary hypertension (PH) frequently complicates the course of patients with IPF and is associated with a myriad of adverse consequences including higher oxygen needs, reduced functional ability, increased healthcare resource utilization, and increased mortality 7,8 . There is a growing appreciation for the importance of the vasculature in the disease process, including possibly being important in the perpetuation of the fibrosis 9 . In support of this, two studies of PH medications have suggested amelioration of the fibrotic process as evidenced by placebo‐corrected improvements in the forced vital capacity 10,11 …”
Section: Introductionmentioning
confidence: 99%
“…Cross-sectional area of subsegmental small pulmonary vessels has been shown to correlate with the extent of CT density measures of emphysema and reflects difference between COPD phenotypes [37,38]. The volume of segmented pulmonary vessels, including arteries and veins but excluding vessels at the hilum, expressed as a percentage of lung volume has been proposed as an independent measure of IPF severity [39][40][41]. Beyond structure perfusion can be assessed using dual-energy CT.…”
Section: Blood Vesselsmentioning
confidence: 99%
“…The assessment of the completeness or integrity of fissures, as a biomarker for collateral flow, was first applied in a subgroup analysis of subjects undergoing endobronchial valve (EBV) placement for treatment of emphysema [45]. In this prespecified analysis, patients with a fissure integrity score >90% of the fissure abutting the treatment lobe were shown to have significant improvement in their forced expiratory volume in 1 s (FEV1) compared to those whose FIS was <90% [41]. The majority of automated fissure detection methods use feature descriptors targeted toward normal fissure anatomy [46][47][48][49][50][51][52][53][54][55][56].…”
Section: Fissuresmentioning
confidence: 99%
“…Physiological parameters like the forced vital capacity (FVC) and transfer lung factor for carbon monoxide (TLCO) do not always represent the extent of fibrosis, and are nondiscriminating from other possible coexistent conditions, such as emphysema or pulmonary hypertension 4 . Using computed tomography (CT), several computer‐generated and visual scores have been reported 4–7 . Visual approaches, however, are inherently subjective.…”
mentioning
confidence: 99%